Mitral Valve Compression Induced Hypoxemia After Left Ventricular Assist Device Surgery: A Case Report. Issue 5 (1st March 2019) - Hosny, Hisham; Hassan, Hesham; Lees, Nicholas; Simon, Andre
Abstract : Blood flow obstruction of left ventricular assist device (LVAD) is not uncommon. Causes of flow obstructions could be prepump, intrapump, and postpump. Clinical and echocardiographic parameters of LVAD obstruction vary substantially, ranging from being completely asymptomatic with unchanged functional status, normal filling pressures to frank cardiogenic shock. In the current case report, we present hypoxemia as an early presentation of LVAD inflow obstruction in the early postimplantation period in the absence of respiratory cause for hypoxemia